The Hidden Struggle: Depression Among Seniors - Magdalena Jabłonowska; Paulina Grzeszczuk (Quality in Sport)
Introduction: This review paper aims to provide a comprehensive analysis of the prevalence, underlying determinants, and treatment modalities of depression in older adults, highlighting the roles of both pharmacological and non-pharmacological interventions.